2020
DOI: 10.1007/s00227-020-3654-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular phosphoesterases of invertebrate origin: underrated actors in phosphorus recycling?

Abstract: Extracellular enzymes contribute substantially to the remineralisation of organic matter in aquatic systems. Marine invertebrates release endogenous enzymes through activities such as sloppy feeding or egestion, but the significance of such processes is widely unexplored. We compared functional key properties such as activity, stability, and apparent molecular masses of extracellular phosphatases from faeces of the marine crustaceans Idotea balthica, Palaemon varians, and Homarus gammarus with those of their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…It has been demonstrated that phagotrophic nanofagellates and marine invertebrates might release extracellular enzymes through major physiological processes such as excretion or sloppy feeding. Recently, active extracellular phosphatase was found in the feces of crustacean species; these can substantially contribute to the pool of active extracellular phosphatases and to the recycling of phosphorus in aquatic systems [47].…”
Section: General Characteristics Of the Pom And Its Relationship With Prokaryotic Variablesmentioning
confidence: 99%
“…It has been demonstrated that phagotrophic nanofagellates and marine invertebrates might release extracellular enzymes through major physiological processes such as excretion or sloppy feeding. Recently, active extracellular phosphatase was found in the feces of crustacean species; these can substantially contribute to the pool of active extracellular phosphatases and to the recycling of phosphorus in aquatic systems [47].…”
Section: General Characteristics Of the Pom And Its Relationship With Prokaryotic Variablesmentioning
confidence: 99%